The Strength of Moulding Sand Consisting of a Mixture of Bentonite, Tapioca Flour, and Sago Flour as a New Binder Formula to Improve the Quality of Al-Si Cast Alloy - Andoko Andoko; Riana Nurmalasari; M. Alfian Mizar; Retno Wulandari; Poppy Puspitasari; Avita Ayu Permanasari (Journal of Mechanical Engineering Science and Technology (JMEST), 2017)
The major factors determining the quality of sand casting products are the base sand and the composition of the sand mould and the binding material. In the foundry industry, the most commonly used binder for creating sand moulds is bentonite. However, the price of bentonite is likely to keep rising. This study aimed at discovering a new binder formula associated with the effect of binder composition i.e. bentonite, tapioca flour, and sago flour on the basis of its mechanical and physical properties. The new formula was expected to be a better binder in the production of sand moulds, resulting in high-quality casting products with minimal defects. Moreover, it is probable to be much more economical than bentonite. This research focused on testing the moulding sand composition with a number of different binders, i.e. bentonite, tapioca flour, and sago flour, each in a different proportion. The mixture of the moulding sand with each of the three binders will be tested in terms of its mechanical properties including compressive, shear, and tensile strength. Based on the test results, sago flour has the highest dry compressive strength of 28.6 N/cm2, whereas bentonite has the highest wet compressive strength, i.e. 11.83 N/cm2 and the highest wet shear strength i.e. 3.16 N/cm2. The binder with the highest dry shear strength is tapioca flour with 18.16 N/cm2. Regarding the tensile strength value, bentonite has the highest wet tensile strength of 0.85 N/cm2, while sago flour has the highest dry tensile strength of 1.73 N/cm2.